Konseling Kelompok dengan Teknik Restrukturisasi Kognitif dalam Mengatasi Homesickness - Intan Mayang Sawitri; Kusnadi Kusnadi (Journal of Society Counseling, 2025)
This study is entitled "Application of Group Counseling with Cognitive Restructuring Techniques in Overcoming Homesickness in Final Year Out-of-School Students of Islamic Guidance and Counseling Study Program". The objectives of this study are: first, to determine the description of homesickness in final year out-of-school students of the Islamic Guidance and Counseling Study Program. Second, to determine the application of group counseling with cognitive restructuring techniques in overcoming homesickness in final year out-of-school students of the Islamic Guidance and Counseling Study Program. This study uses a qualitative research method that is descriptive in nature, with field research or direct field research. Data collection techniques used are by means of observation, interviews, and documentation. The results of this study indicate a strong emotional attachment to family or the home environment, so that feelings of sadness, anxiety, longing, and even excessive worry about family arise when away from home. The stages of this group counseling were carried out four times with subjects selected as five final year out-of-school students of the Islamic Guidance and Counseling Study Program, using four stages, namely the formation stage/initial stage, transition stage, activity stage, and closing stage. Based on research conducted using cognitive restructuring techniques, which are able to change negative thoughts into positive/rational thoughts in group counseling activities during the activity.